2021
DOI: 10.3390/buildings12010024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Process of Synthesis of Zeolites from Volcanic Ash in Its Synergistic Action as a Flame-Retardant for Polypropylene Composites

Abstract: In this research, the influence of natural zeolites obtained from the volcanic ash of the Ubinas volcano has been studied as synergistic agents in a flame-retardant system (composed of ammonium polyphosphate, pentaerythritol, and polypropylene). Four zeolites were synthesized from volcanic ash, including those that had been calcined and those that had not. These were then placed in an alkaline solution at three synthesis temperatures. Zeolites were characterized through X-ray diffraction, specific surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Indeed, the angular shape of this volcanic material indicates its recent origin and freshness, since remobilized volcanic particles would display more rounded angles. The detrital‐like Boström index can therefore be attributed to the predominance of volcanic‐derived particles, a material reported as Mn‐poor but Fe and Al‐rich (Figure 5b; e.g., Almirón et al., 2021; Fiantis et al., 2010; Leonelli et al., 2007; Naji and Asi, 2008; Oskarasson, 2010; Razzhigaeva et al., 2009; Tchakoute Kouamo et al., 2012). LSi EF at 1,000 m provides further evidence, as this element has been reported to be enriched in volcanic material relative to pelagic ones (Bailey, 1993; Fiantis et al., 2010; Li and Schoonmaker, 2003; Sayles and Bischoff, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the angular shape of this volcanic material indicates its recent origin and freshness, since remobilized volcanic particles would display more rounded angles. The detrital‐like Boström index can therefore be attributed to the predominance of volcanic‐derived particles, a material reported as Mn‐poor but Fe and Al‐rich (Figure 5b; e.g., Almirón et al., 2021; Fiantis et al., 2010; Leonelli et al., 2007; Naji and Asi, 2008; Oskarasson, 2010; Razzhigaeva et al., 2009; Tchakoute Kouamo et al., 2012). LSi EF at 1,000 m provides further evidence, as this element has been reported to be enriched in volcanic material relative to pelagic ones (Bailey, 1993; Fiantis et al., 2010; Li and Schoonmaker, 2003; Sayles and Bischoff, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…A Study on the Improvement of Flame-Retardant Performance for the Use of Construction Finishing Materials in Paper Beehive [13] Vojta et al (2017) Statistical analysis of the type and content of flame retardants used [14] Almirón et al (2022) Analysis of the effect of zeolites of volcanic ash on the synergistic effects of flame-retardant systems [15] Han et al (2022) Development and verification of PLA composite materials with improved flame retardants through the mixing of polylactic acid (PLA) and flame retardant [16] Guo (2022) Development of flame-retardant polystyrene composite panels using magnesium hydroxide flame retardant [17] The recycling ratio of paper waste generated worldwide is only up to 65%, and efforts are being made to improve recycling rates [18]. This study reviews the use of wastepaper as a building finishing material with flame-retardant properties, incorporating a recycling method for wastepaper.…”
Section: Rie Et Al (2012)mentioning
confidence: 99%
“…Almirón et al confirmed that natural zeolites collected from volcanic ash affect the synergistic action of flame-retardant systems comprising ammonium polyphosphate, pentaerythritol, and polypropylene [15].…”
Section: Introductionmentioning
confidence: 97%
“…The higher Boström index at 1000 m (~40 to 66; Table 3) can therefore be attributed to the predominance of volcanic-derived particles, a material reported as Mn-poor but Fe and Al-rich (Fig. 5b; e.g., Almirón et al, 2021;Fiantis et al, 2010;Leonelli et al, 2007;Naji and Asi, 2008;Oskarasson, 2010;Razzhigaeva et al, 2009;Tchakoute Kouamo et al, 2012). It also explains the high estimated LSiEF at 1000 m (x14 relative to reference pelagic clays) as this element has been reported to be enriched in volcanic material relative to pelagic ones (Li and Schoonmaker, 2003;Sayles and Bischoff, 1973;Bailey, 1993;Fiantis et al, 2010).…”
Section: Along the Tonga Arc (Small Scale)mentioning
confidence: 99%